A review of extractions of seaweed hydrocolloids: Properties and applications - H. P. S. Abdul Khalil (eXPRESS Polymer Letters, 2018)
The term hydrocolloid generally refers to substances that form gels or provide viscous dispersion in the presence of water. Alginate, agar, and carrageenan are three commercially valuable hydrocolloids derived from certain brown and red seaweed and each has their distinct physicochemical properties (i.e. functional and bioactive). Various applications of these seaweed hydrocolloids as thickeners, stabilizers, coagulants and salves (in the wound and burn dressings) and materials to produce bio-medical impressions in the food, pharmaceutical, and biotechnology industries are highlighted in this review. Although the existing industrial methods of extraction for these seaweed hydrocolloids are well-established, still growing demand has exposed certain limitations of those methods, notably efficiency and product consistency. In order to achieve targeted hydrocolloids for specific purposes and functionalities, some novel and green extraction methods have also been proposed and discussed. Microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), enzyme-assisted extraction (EAE), supercritical fluid extraction (SFE), pressurized solvent extractions (PSE), reactive extrusion and photobleaching process are selectively presented as highly promising candidates that can avoid the use of chemicals and provide novel means of access to seaweed hydrocolloids with both economic and environmental benefits. However, this review does not provide the ‘best’ method or procedure as many are still under development. Hence, the review gives ‘food for thought’as to new processes which might be adopted industrially and concluded that further research is required in order to contribute additional new knowledge and refinement to this field of study.